Case Report: Benign Infantile Seizures Temporally Associated With COVID-19 - García-Howard, Marcos; Herranz-Aguirre, Mercedes; Moreno-Galarraga, Laura; Urretavizcaya-Martínez, María; Alegría-Echauri, Josune; Gorría-Redondo, Nerea; Planas-Serra, Laura; Schlüter, Agatha; Gut, Marta; Pujol, Aurora; Aguilera-Albesa, Sergio (Frontiers in Pediatrics, 2020)
Background: Nonfebrile illness seizures may present in previously healthy children as afebrile seizures associated with minor infections, such as mild gastroenteritis or respiratory tract infections, with a genetic predisposition. For the novel human coronavirus SARS-CoV-2 causing COVID-19, fever, cough and gastrointestinal complaints are the most common symptoms in children and a hyperimmune response may be present. No detailed temporally associated neurological complications have been documented in pediatric case series so far. Case description: We present the case of a 3-month-old girl with nonfebrile repeated seizures in a COVID-19 family setting. The infant started with mild fever and cough that lasted two days. At day 6 from onset, the girl presented two focal motor seizures with impaired consciousness and awareness. All investigations ruled out signs of meningo-encephalitis or active epilepsy, including normal electroencephalogram and cerebral magnetic resonance imaging. PCR from nasal and throat swabs was positive for SARS-CoV-2. Remarkably, blood ferritin and D-dimer levels were increased. At day 9, the infant presented another afebrile motor seizure and levetiracetam was started, with favourable response in 3 months of follow up. Much interest has raised on host genetic determinants to disease severity and susceptibility to COVID-19. We thus performed whole exome sequencing, revealing a pathogenic frameshift mutation in PRRT2 gene, in both the mother and the infant. The mother had presented two late infantile febrile convulsions with normal outcome afterwards. Discussion: The hyperimmune response described in adult cases with COVID-19 can be displayed by infants, even in absence of respiratory symptoms. Moreover, COVID-19 disease may present in infants as nonfebrile seizures, triggering early onset seizures in infants with a genetic predisposition. In this pandemic situation, precision medicine using massive sequencing can shed light to reveal underlying molecular mechanisms driving the host response to COVID-19.